Prospects of Creating Memorable Experience in Nepalese Tourism and Hospitality Industry - Rijal, Chanakya P; Ghimire, Sudip (Journal of Tourism and Hospitality Education, 2016)
This paper contributes to explore the concept of experience economy theory of Pine and Gilmore (1998) as a basis for measuring the prospects of creating memorable experience in Nepalese tourism and hospitality industry identifying the key elements of Nepalese tourism and hospitality industry and its dimension based on the four realms of experience as proposed by the author of experience economy theory. For assessing this result, an ethnographic study based on semi-structured interview were conducted with leading professional of Nepalese tourism and hospitality field and also with a visitor. The result of the study has clearly depicted and further elaborated the Nepalese key elements of tourism and hospitality experience, present status, major attributes, underlying anticipation of the industry, illustrating the implication while focused on the various core elements and the indigenous attributes of Nepalese tourism and hospitality industry. However, the results are confined only with the prospects based on the confirmation of the scope in experience economy for this industry with very little focus on the prospects for designing further experience or staging the experience. It has also served as a basis for understanding the emergent theory in experiential consumption of tourism and hospitality services in Nepalese sector that can be applied to the varying stage of development in the promotion and marketing of tourism and hospitality service offering. Consequently, it has also offered a new theoretical direction for tourism and hospitality policy makers, planners as well as a practical insight for the contemporary application of the findings for marketers and decision makers.Journal of Tourism and Hospitality Education (Vol. 6) Page: 40-66